Conformity confirmation mechanics of photovoltaic equipment in Russia. (November 2020) - Shepovalova, Olga V.; Ivanov, Alexey V.
Abstract: This article deals with the research of the conformity confirmation mechanics in Russian and the CIS countries and their application for confirming the photovoltaic equipment conformity. The conformity confirmation mechanics for photovoltaic equipment and renewable energy sources (RES)-based equipment as a whole in the world are now at the stage of formation. That being said, one of the main problems related to photovoltaic equipment is the problem of inconformity of the output parameters specified in the technical documentation and expected by the consumers with the parameters in the course of operation. Also important is the coordination of the photovoltaic equipment parameters and particularities with the parameters, operating modes, and control rules of electric energy system equipment when integrating photovoltaic systems into Russian centralized power supply systems. That is why research in this area is topical and of considerable interest. The existing conformity confirmation systems in the Russian Federation and Eurasian Economic Union (Customs Union) are considered and compared with the conformity confirmation on the basis of the International Electrotechnical Commission standards. The international experience and its applicability in Russia are analyzed. The conformity confirmation mechanics, their possible and necessary modifications, and peculiarities of photovoltaic equipment conformity assessment are considered. The existing problems and ways of their solution are analyzed.